Gambaran Pelaksanaan Kegiatan Kelas Ibu Hamil Di Wilayah Kerja Puskesmas Mranggen Kabupaten Demak Description Of Implementation Of Pregnancy Class In Worked Area Of Public Health Centre Mranggen District Demak Regency - Rini Puspita Sari; Syamsulhuda Budi Mustofa; Kusyogo Cahyo (Jurnal Kesehatan Masyarakat (Undip), 2014)
Bacground:  The  high  maternal  mortality  rate  (MMR)  and  Infant  Mortality  Rate  (IMR)  in Indonesia  related  to  pregnancy,  childbirth,  and  postpartum  so  that  one  of  promotive  and preventive health ministry began intensively conducted the Pregnancy It’s means to learned together about pregnant women health form of face-to-face in groups. The purpose of this research to describe the implementation of pregnancy class in worked area of public health centre Mranggen district Demak regency. Method ;  The research was conducted at  Mranggen Public Health Centre and a qualitative research  method  depth  interview.  Midwives  15  key  informants  selected  by  purposive sampling. The  validity  of  the  data  used  by  the  source  triagulasi  methods  that  follow  the activity of Pregnancy Pregnancy classes and midwife coordinator. Result ; The results showed the picture of the implementation of the implementation class of pregnant women in health centers Mranggen Demak is good enough it is seen from  POAC (planning,  organizing,  actuating  dan  controling)  the  planning  still  exist  that  do  not  have  a plan,  with  a  fairly  good  organizing  with  the  cooperation  with  relevant  parties  Viewed actualing  between  planning  and  execution  is  appropriate,  whereas  views  control,  in  each level of each already have a person in  charge, and full reporting and routine every month. Conclusions;  Direct supervision of a midwife coordinator advised to not rely solely on the monthly report